Antihyperglycaemic effects of ethanol extracts of andrographis paniculata on streptozotocin-induced diabetic rats - Kasmuri, Abdul Razak; Ahmad, Mariam; Asmawi, Mohd Zaini (Universiti Malaya, 2005)
Single oral dose administration of 20% ethanol extract of Andrographis paniculata (Acanthacaea) was found not to lower the blood glucose level of streptozotocin-induced diabetic rats but inhibited the rise in blood glucose level of glucose loaded normal rats in glucose tolerance test. The present study was conducted to determine the effect of chronic administration of different ratios of aqueous ethanolic extracts of this plant on the blood glucose levels of diabetic rats as well as their effect on insulin levels. Six groups of streptozotocin-induced diabetic rats (n=6) were treated orally either with metformin (0.5 g/kg body weight), tap water, 20%, 50%, 95% ethanolic or water extracts of A. paniculata (0.5 g/kg body weight) twice daily for fourteen days respectively. The results showed that only the blood glucose levels in 50% and 95% ethanol extracts treated rats were significantly reduced (p<0.05). It suggests that the antidiabetic compound(s) in this plant is/are relatively non polar and different from the compound(s) that inhibit the increase of blood blucose levels in glucose loaded normal rats. Moreover, different extracts were subjected to thin layer chromatography (TLC). The results showed that the presence of andrographolide in all the different ratios of aqueous ethanolic extracts examined. However, it is still to be determined how andrographolide, found in these plant extracts contributed to the differences in mechanisms of actions.